Pengaruh Kualitas Produk, Desain Produk Dan Citra Merek Terhadap Keputusan Pembelian Sepeda Motor Honda Beat Dealer Nusantara Sakti Jakarta Barat - Fitra Pratama Putra; Suadi Sapta Putra; Kumba Digdowiseiso (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to determine the effect of the t test on product quality, product design and brand image variables on purchasing decisions. The sample in this study was 100 respondents who made a decision to purchase a Honda Beat motorcycle dealer Nusantara Sakti. Inferential analysis technique with multiple linear regression and using Statistical Product and Service Solution (SPSS) version 20. From the t test results show that the Product Quality variable (X1) does not have a large influence 0.498 < 1.984 Product Design variable (X2) does not have a significant effect 0.828 < 1.984 and Brand Image (X3) has an influence of 8.098 > 1.984 on purchasing decisions. It can be concluded that product quality and product design have no effect on purchasing decisions and brand image variables affect purchasing decisions. Keywords: Product Quality, Product Design, Brand Image and Purchase Decision.